2009
DOI: 10.1128/aem.00272-09
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Enterotoxin Gene Profiles among Clonal Complexes of Staphylococcus aureus Isolates from the Bronx, New York

Abstract: Staphylococcal enterotoxins (SE) can cause toxin-mediated disease, and those that function as superantigens are implicated in the pathogenesis of allergic diseases. The prevalence of 19 enterotoxin genes was determined by PCR in clinical S. aureus strains derived from wounds (108) and blood (99). We performed spa typing and multilocus sequence typing (MLST) to determine clonal origin, and for selected strains staphylococcal enterotoxin B (SEB) production was measured by enzyme-linked immunosorbent assay. Strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
102
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(125 citation statements)
references
References 60 publications
17
102
6
Order By: Relevance
“…ϳ0.75 Å). Our data identify 17 residues of SEB that bind 20B1 Fab , which are conserved among SEBs derived from diverse clinical methicillin-sensitive and -resistant Staphylococcus aureus strains (49). Interestingly, of those 17 residues, 14 are identical in SEC1, and 11 are identical in SEC2 and SEC3, and 10 are identical in SSA.…”
Section: Discussionmentioning
confidence: 83%
“…ϳ0.75 Å). Our data identify 17 residues of SEB that bind 20B1 Fab , which are conserved among SEBs derived from diverse clinical methicillin-sensitive and -resistant Staphylococcus aureus strains (49). Interestingly, of those 17 residues, 14 are identical in SEC1, and 11 are identical in SEC2 and SEC3, and 10 are identical in SSA.…”
Section: Discussionmentioning
confidence: 83%
“…Epidemiological studies have demonstrated the SEl-K-encoding genes to be among the most common SE genes in S. aureus clinical isolates (10-14). Additionally, SEl-K is the only SE gene to our knowledge that is significantly associated with community-acquired methicillin-resistant S. aureus (CA-MRSA) strains of several clonal lineages (10,15,16). Interestingly, the neighboring SEl-Q enterotoxin is not significantly associated with MRSA (10).…”
mentioning
confidence: 99%
“…In this study, we compared the prevalences of PVL in MSSA and MRSA strains from patients with skin and soft tissue infections (SSTIs) and compared the clinical presentations. S. aureus isolates from wound (n ϭ 108) and blood (n ϭ 99) were collected by the microbiology laboratory of Montefiore Medical Center as described previously (9). Detection of enterotoxin genes (staphylococcal enterotoxin A [SEA], SEB, SEC, and toxic shock syndrome toxin [TSST] genes), multilocus sequence typing (MLST), and spa typing were done in the context of a previously published study (9).…”
mentioning
confidence: 99%
“…S. aureus isolates from wound (n ϭ 108) and blood (n ϭ 99) were collected by the microbiology laboratory of Montefiore Medical Center as described previously (9). Detection of enterotoxin genes (staphylococcal enterotoxin A [SEA], SEB, SEC, and toxic shock syndrome toxin [TSST] genes), multilocus sequence typing (MLST), and spa typing were done in the context of a previously published study (9). For this study, detection of PVL in MSSA isolates was performed by real-time PCR targeting the lukF-PV gene (7).…”
mentioning
confidence: 99%